Physical preparation and return to performance of an elite female football player following ACL reconstruction: a journey to the FIFA Women's World Cup. Issue 1 (1st December 2020) - Taberner, Matt; van Dyk, Nicol; Allen, Tom; Jain, Neil; Richter, Chris; Drust, Barry; Betancur, Esteban; Cohen, Daniel D
Abstract : ACL injuries are among the most severe knee injuries in elite sport, with a high injury burden and re-injury risk. Despite extensive literature on the injury and the higher incidence of injury and re-injury in female athletes, there is limited evidence on the return to sport (RTS) of elite female football players following ACL reconstruction (ACLR). RTS is best viewed on a continuum aligning the recovery and rehabilitation process with the ultimate aim — a return to performance (RTPerf ). We outline the RTS and RTPerf of an elite female football player following ACLR and her journey to the FIFA Women's World Cup, including the gym-based physical preparation and the on-pitch/sports-specific reconditioning. We used the 'control–chaos continuum' as a framework for RTS, guiding a return above pre-injury training load demands while considering the qualitative nature of movement in competition. We then implemented the 'RTPerf pathway' to facilitate a return to team training, competitive match play and a RTPerf . Objective information, clinical reasoning and shared decision-making contributed to this process and helped the player to reach her goal of representing her country at the FIFA Women's World Cup.